PENATALAKSANAAN DISFUNGSI MENELAN PADA PENDERITA STROKE AKUT DI UNIT STROKE - Sitti Airiza Ahmad* (Neurona Majalah Kedokteran Neuro Sains, 2011)
AIM TO IDENTIFY THE INCIDEMCE AND THE RECOVERY OF SWALLOWING FUNCTION IN ACUTE STROKE PATIENTS WHO WERE TREATED USING STANDARD METHOD IN UNIT STROKE DR CIPTO MANGUNKUSUMO HOSPITAL